2019
DOI: 10.3390/cells8121564
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of miRNAs in Human Ovaries, Oocytes, Extracellular Vesicles, and Early Embryos: A Systematic Review

Abstract: The recent discovery of microRNAs (miRNAs) in human reproductive tissues and cells indicates a possible functional role in reproductive function. However, the studies published to date in female reproductive tissues/cells and embryos are inconclusive and sometimes controversial. In order to update the knowledge of this field, the present study aimed to discuss, through a systematic review, the role of miRNAs in female human reproduction and early embryogenesis. We conducted a systematic review of the published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 57 publications
2
31
0
1
Order By: Relevance
“…Further, they reported that knockdown of miR-320a expression in mouse metaphase-II oocytes resulting in embryos arrested at rst cleavage. While very few can develop into top-quality embryos, indicating that the miR-320a has a potential role in modulating gene expression and regulating embryonic development [37].…”
Section: Discussionmentioning
confidence: 99%
“…Further, they reported that knockdown of miR-320a expression in mouse metaphase-II oocytes resulting in embryos arrested at rst cleavage. While very few can develop into top-quality embryos, indicating that the miR-320a has a potential role in modulating gene expression and regulating embryonic development [37].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of miRNAs has been confirmed throughout the growth and maturation of mammalian oocytes [100], and they have a critical role in the physiology and developmental competence of mammalian oocytes and embryos. Furthermore, a recent review provided evidence that aberrant miRNA expression in female reproductive cells and embryos is associated with infertility and embryogenesis defects [101].…”
Section: Epigenetic Information Through Small Rnasmentioning
confidence: 99%
“…También se han encontrado cambios en el grado de metilación de las histonas H3 y H4 asociado con restricción calórica y trastornos de aprendizaje [1][2][3] ; y en el contenido de miARN en oocitos y espermatozoides. Estos miRNA regulan la modificaciones post-traduccionales de las histonas y afectan el neurodesarrollo fetal 5,6 . Al respecto, recientemente Chan y cols.…”
Section: The Inheritance Of Covid-19 Pandemicunclassified